Laicidad and Religious Diversity in Latin America - Vaggione, Juan Marco; Morán Faúndes, José Manuel (Springer International Publishing : Imprint: Springer, 2017)
This book presents revealing reflections on historical, socio-political, and legal aspects, as well as their contexts, in Argentina, Bolivia, Colombia, Costa Rica, Ecuador, Mexico, and Peru. Further, it includes theoretical and empirical analyses that identify the connections between religion and politics that characterize Latin American countries in general. The individual chapters are based on a dialogue between regional and international approaches, renewing them and taking them to their limits by incorporating the Latin American experience. The book reflects the current intensification of research on religion in Latin America, the resulting reassessment of previous approaches, and the strengthening of empirical studies. It provides vital insight into the ways in which politics regulates the religious sphere, as well as how religion modulates and intervenes in politics in Latin America. In doing so it builds a bridge between the findings of researchers in the region on the one hand and the English-speaking academic public on the other, contributing to a dialogue that enriches comparative perspectives. .
Keywords: Social sciences.; Religions.; Latin America -- Politics and government.; Religion and sociology.; elektronické knihy; electronic books